Half-dose may be equivalent to full-dose anticoagulants in preventing venous thromboembolism after primary total joint arthroplasty: a single center comparative retrospective cohort study - Wang, Yinghao; Liao, Zhixin; Zhou, Zongke; Wang, Haoyang (Frontiers in Pharmacology, 2025)
BackgroundThe optimal anticoagulant administration for deep vein thrombosis (DVT) prevention following total joint arthroplasty (TJA) remains controversial. We aimed to compare the effectiveness and safeness of half-dose and full-dose anticoagulant regimen in preventing DVT following TJA surgery.MethodsThis study was designed as a retrospective comparative analysis. All eligible patients received DVT prophylaxis within 2 weeks postoperatively, consisting of enoxaparin (first 2 days) and rivaroxaban (subsequent 12 days). According to the dosage of anticoagulant, patients were divided into a half-dose group (0.2 mL enoxaparin sodium and 5 mg rivaroxaban) and a full-dose DVT prophylaxis group (0.4 mL enoxaparin sodium and 10 mg rivaroxaban). The occurrence of DVT and pulmonary thromboembolism (PE) within 2 weeks postoperative, total blood loss (TBL) during the use of anticoagulants. WOMAC scores recorded at 12 months postoperative were compared between the two groups.ResultsA total of 1886 patients were enrolled in this study, including 1,246 in the half-dose group and 640 in the full-dose group. No cases of PE were reported in the two groups. The DVT was detected in 11 patients (0.9%) in the half-dose group, which was not significantly different from 8 patients (1.3%) in the full-dose group, p = 0.648. Also, the WOMAC scores were comparable between the half-dose group (11.11 ± 18.01) and the full-dose group (8.88 ± 15.33), p = 0.393. Contrastively, the TBL (560.88 ± 307.69 mL) and average hospital stay (4.73 ± 1.50 days) were significantly lower in the half-dose group than that in the full-dose group (653.95 ± 333.70 mL, 5.74 ± 2.36 days), p < 0.001.ConclusionHalf-dose of DVT prophylaxis drugs during the perioperative period of TJA does not elevate DVT incidence. Furthermore, it significantly decreases TBL and shortens hospital stays, while having no adverse impact on postoperative joint function recovery. These findings may support the implementation of half-dose protocol anticoagulants in the TJA protocol.